Hair determination from bird nests in urban environments - Patkó, László; Ujhegyi, Nikolett; Heltai, Miklós (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
The aim of our study was to test a new noninvasive method, the bird-nest analysis in urban environment. Our first study area was at Merzse-swamp (2011), which is located in the south-west of Budapest. The other study areas were the University Park and the Lower Park at Gödöllő (2012). Study was based on collecting mammal hairs from bird nests. It was necessary to record some macroscopic features of the hairs during the identification (color, shape, length) and four microscopic features, (1) the cuticula scale pattern at the shaft and (2), at the thickest part of the shield, the medulla structure at the thickest part of the shield without oil penetration (3), and with oil penetration (4). At Merzse-swamp we were able to categorize the following groups: brown rat (Rattus norvegicus), European hare (Lepus europeus), weasel-erminea (Mustela nivalis-M. erminea), European otter (Lutra lutra), edible dormouse (Glis glis), human (Homo sapiens), hazel dormouse-forest dormouse (Muscardinus avellanarius-Dryomis nitedula), canids (Canidae), bats (Chiroptera), rodents (Rodentia) and unidentified (Unident.). At Gödöllő the categories were as follow: European hare (Lepus europeus), horse (Equus caballus), European mole (Talpa europea), dog (Canis familiaris), hazel dormouse (Muscardinus avellanarius), human (Homo sapiens) and unidentified (Unident.). According to our study it has been demonstrated that the nest- analysis can be a useful technique for researchers and urban wildlife management experts, but references from hairs and practice are necessary to get familiar with the method.
Keywords: noninvasive methods; bird nest analysis; urbanization; hair morphology; Gödöllő; Merzse-swamp